A logomarca na cena do acontecimento: riscos das estratégias perante a circulação da marca pelos espaços sociais - Thieme, Robert (Universidade do Vale do Rio dos Sinos, 2012)
The master’s thesis aims to understand the brand’s movement through the social spaces, covering the process that accept and manage the identity until to the a individual experience aggregation, media, urban environments and events that the brands interact.The investigation of this way happens through a studyperspective of the mediatization beyond to the strategies of institutions (journalism and publicity, and others) in the production and reception sphere, accentuating the movement as a process that produce another sense about brand. We found that the mesh from this process potentiates the speeches and enable a considerable brand’s proliferation through the several instances of the social level.We certify that this generality is reflected in the newspapers photos which we verified the presence of many brands in the main press’s pictures.We collected many corpus in the Zero Hora and Folha de São Paulo newspaper and the subject were categorized and analyzed.This investigation allowed the discussion about brand’s movement characteristic through social spaces ending up by these specific cases in the interaction between journalism and publicity.
Keywords: Marcas publicitárias; Espaços sociais; Fotojornalismo; Circulação; Brands; Social spaces; Photojournalism; Circulation; ACCNPQ::Ciências Sociais Aplicadas::Comunicação